FISCAL COMPOSITION OF LOCAL BUDGETS IN THE CONTEXT OF FINANCIAL DECENTRALIZATION (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The purpose of the article is to determine the role of the fiscal component of local budgets in the context of financial decentralization.Sustainable development of the state and its regions is determined by the budget potential of a separate administrative-territorial unit, that is, the volume of own and attracted financial resources accumulated in the local budget. Internal fiscal potential is seen as an important financial priority for economic growth in the region. The fiscal potential should ensure the positive dynamics of the development of the territory and create a competitive environment.The new modern model of society management, built in the context of the reform of the territorial organization of power, is based on the creation of financially self-sufficient communities. Local taxes and fees are one of the important sources of local government budget revenue generation. Starting from 2014, the share of local taxes and fees grows in the revenues of local budgets of Ukraine. Such changes are due to the improvement of tax and budgetary legislation, as well as the interest of local self-government bodies in additional mobilization of revenues to local budgets. Therefore, increasing the role of local taxes and fees, as well as increasing their share in local budgets' own revenues, is one of the main tasks of the fiscal policy of the state.One of the innovations that will positively affect local budget revenues is the introduction of a land tax for forest land and the establishment of a tax rate per hectare of forest land. That is, local budgets are able to get additional resources through the taxation of forest lands. It is also assumed that the deduction of personal income tax for leased land should be carried out at the location of such facilities. Another new source of revenue generation for local government budgets is a 5% rent for the use of mineral resources for the extraction of minerals of national significance. The payment will be received at the place of extraction of minerals in full size.Consequently, the establishment and collection of local taxes and duties is one of the effective mechanisms for the formation of the resource potential of local self-government bodies. The size of local taxes depends on the effective organization of work on their introduction and collection. In addition, it is important to effectively secure consolidated national taxes, such as personal income tax, excise and rent payments. Local governments have real opportunities to influence the volume of revenues from local tax payments to the respective budgets through the introduction and setting of the rates. Therefore, it is important and timely to create a resource and material base of local importance, as well as identify ways to increase its fiscal potential. This should positively affect the financial self-sufficiency of local budgets.
Keywords: local budget, budget capability, fiscal policy, local taxes and fees.